Analisis Kinerja Keuangan Pada Klub Sepak Bola (Studi Kasus Pada Arsenal, Tottenham Hotspur dan Everton) - Elvina Chandra Pranata; Supatmi Supatmi (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
Football is a popular sport that affect various aspects of life, one of which is the economy. In Europe, football has become an industry and the clubs most are already preparing financial statements. This study aims to analyze the financial performance of three football clubs that followed the Premier League as one of the best leagues in the world, Arsenal, Tottenham Hotspurs and Everton, for the period of 2007-2011. This study uses the technique of quantitative and qualitative descriptive analysis using 14 financial ratios relevant to the football club. Results showed in general Arsenal is a club that has the best financial performance in comparison Tottenham Hotspurs and Everton, in particular in such matters, income and liquidity. Tottenham Hotspurs have advantages in terms of net investment over player contracts and operating cash flow. While Everton in general have the worst financial performance in terms of operations and liquidity, but has a good asset turn over.